The Development of Speaking Teaching Model at SMP Negeri I Muaro Jambi - Yelia Yelia (Universitas Negeri Padang, 2014)
Based on the writer’s observation and interview with some English teachers in Jambi Province, the writer concludes that the teaching of speaking is the biggest problem they have. Because of that, the writer conducted a research at one of junior high schools in Jambi Province, SMP Negeri 1 Muaro Jambi, to investigate the model used by the English teachers and develop it. The writer investigated the model usually used by teachers by doing observation when the process of teaching ‘Descriptive Text’ took place and interviewing the English teachers. Then, the model was described in five structures namely syntax, the social system, principles of reaction, support system, and effects of the model. After that the writer developed it into the new model called Ci-Y model. The next step, the writer conducted a quasi experimental research to know the effectiveness of the two models. The populations of the research were the first grade students which consisted of six classes. The samples were two equivalent classes namely class B and F. Class B was taught with Teacher Model and class F with Ci-Y Model. At the end of the research, the two classes had speaking test. The result of test showed that Ci-Y Model was more effective than the model usually used by the teacher. It also showed that score of class F was higher than class B.